A Comparison of Patient-Reported Outcomes After Nipple-Sparing Mastectomy and Conventional Mastectomy with Reconstruction - Romanoff, Anya (Ann Surg Oncol, 2018)
INTRODUCTION: Nipple-sparing mastectomy (NSM) is increasingly used for breast cancer risk reduction and treatment. Prior small studies with variable control for baseline characteristics suggest superior satisfaction with NSM. The aim of this study was to compare patient satisfaction following NSM and total mastectomy (TM) utilizing the BREAST-Q patient-reported outcome measure in a well-characterized patient population. METHODS: Patients at a single institution undergoing NSM or TM with immediate tissue expander/implant reconstruction who completed a follow-up BREAST-Q from 2007–2017 were identified by retrospective review of a prospective database. Baseline characteristics were compared, and linear mixed models were used to analyze associations with BREAST-Q scores over time. RESULTS: Of 1866 eligible patients, 219 (12%) underwent NSM, and 1647 (88%) underwent TM. Median time from baseline to BREAST-Q was 658 days. Patients having NSM were younger, more likely to be white, and had lower BMI. They more often had prophylactic surgery, bilateral mastectomies, lower-stage disease, and less often received chemotherapy/radiation than patients having TM. On multivariable analysis, after controlling for relevant clinical variables, there was no difference in satisfaction with breasts or satisfaction with outcome overall between NSM and TM patients. Psychosocial well-being and sexual well-being were significantly higher in the NSM group. After additionally controlling for pre-operative BREAST-Q score in a subset of patients (72 NSM; 443 TM), only psychosocial well-being remained significantly higher in NSM patients. CONCLUSION: Patient-reported outcomes should be discussed with women weighing the risks and benefits of NSM to provide a better understanding of expected quality of life.